Left common carotid artery arising from the brachiocephalic trunk: a case report - Paraskevas, Georgios (BioMed Central, 2008)
An abnormal origin of the left common carotid artery from the initial portion of the brachiocephalic trunk was found in the superior mediastinum in a 81-year-old Caucasian male cadaver during dissection practice. We report on the exact morphology of that variant that is appeared in an incidence of 0,2% in the literature. We discuss the relative literature and pay attention on the significance of such a variation for clinicians in its recognition and protection.